Contextual factors associated with the use of corporal punishment in U.S. public schools. (August 2017) - Font, Sarah A.; Gershoff, Elizabeth T.
Highlights: We examined correlates of school corporal punishment (SCP) use and disparities. Cultural, socioeconomic, and racial characteristics all predicted SCP use. School and county racial composition predicted disparate use against Black students.